X-ray fluorescent spectral analysis in forensic medical assessment of injuries caused by electric shock devices - V. D. Mishalov; Y. A. Varfolomeiev (Kazimierz Wielki University, 2021)
Introduction and purpose. Electroshock devices are a type of non-lethal weapon and are widely used. The systematized data concerning the forensic medical assessment of injuries caused by electric shock devices are extremely limited. The purpose of the study was to increase the efficiency of forensic assessment of injuries caused by electroshock devices by using the methods of elemental analysis, namely, X-ray fluorescence spectral analysis. Methods. During the experiment, the electric discharges were applied to the skin flaps using electric shock devices under two conditions, namely, in close contact of the ESD electrodes with the skin and from a distance of 3-5 mm. A macroscopic study of skin changes obtained due to the electric impact of electric shock devices was carried out, as well as X-ray fluorescence spectral analysis to establish qualitative and quantitative indicators of the chemical elemental composition of the studied objects. Results. It was found that under the condition of causing damage from a distance the formation of macroscopically visible changes resembling the typical electric burn was observed. No increase in the concentration of chemical elements (metals) is determined in all samples of biological material after the impact of electric discharges of ESD in this condition. Under the condition of close contact of the electrodes of electric shock devices with the surface of the skin no macroscopically distinguishable lesions were found on the skin. The XRF spectral analysis revealed metal deposits in the areas of skin flaps that were subject to ESD. Conclusion. The XRF spectral analysis can be useful tool for objective confirmation of the action of electroshock devices.